2023
DOI: 10.1002/cam4.6131
|View full text |Cite
|
Sign up to set email alerts
|

The genetic polymorphisms of immune‐related genes contribute to the susceptibility and survival of lymphoma

Abstract: BackgroundThough immunological abnormalities have been proven involved in the pathogenesis of lymphoma, the underlying mechanism remains unclear.MethodsWe investigated 25 single nucleotide polymorphisms (SNPs) of 21 immune‐related genes and explored their roles in lymphoma. The genotyping assay of the selected SNPs was used by the Massarray platform. Logistic regression and Cox proportional hazards models were used to analyze the associations of SNPs and the susceptibility of lymphoma or clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…A20 rs77191406 is a prognostic marker for rapid malignancy progression and poor survival of rheumatoid arthritis and systemic lupus erythematosus patients [16]. The IFNγ rs2069718 is associated with NHL patients' survival [9] and the risk of developing severe COVID-19 disease, which is caused by abnormally high levels of cytokines such as IFN-γ, IL-6, and TNF-α [20]. In addition, carriers of the JAK2 rs10974947 are linked to polycythemia vera susceptibility [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A20 rs77191406 is a prognostic marker for rapid malignancy progression and poor survival of rheumatoid arthritis and systemic lupus erythematosus patients [16]. The IFNγ rs2069718 is associated with NHL patients' survival [9] and the risk of developing severe COVID-19 disease, which is caused by abnormally high levels of cytokines such as IFN-γ, IL-6, and TNF-α [20]. In addition, carriers of the JAK2 rs10974947 are linked to polycythemia vera susceptibility [13].…”
Section: Resultsmentioning
confidence: 99%
“…The immunogenetic investigations revealed that inflammation-related genes, including tumor necrosis factor α-induced protein 3 (TNFAIP3, A20), tumor suppressor cylindromatosis (CYLD), interferon (IFN)γ, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PI3KCA), Janus kinase (JAK)2, tyrosine kinase (TYK)2 and tumor protein (TP)53 are associated with the survival, proliferation, and progression of tumor cells [6][7][8][9][10][11][12][13][14][15][16]. In our recent study, inactivations of A20 and CYLD lead to the pathogenesis of lymphomas [17][18][19].…”
Section: Introduction *mentioning
confidence: 99%
See 1 more Smart Citation
“…3.4 Clinical significance of IL-6 (−634G>C) and IL-6R (48892A>C) genetic polymorphisms in non-small cell lung cancer patients treated with ICIs IL-6 or IL-6R genetic polymorphisms have been reported to be associated with risk or prognosis in patients with some cancers (DeMichele et al, 2009;Motoyama et al, 2012;Stephens et al, 2012;Kibe et al, 2014;Ruzzo et al, 2014;Zhang et al, 2017;Gu et al, 2023). Therefore, we investigated the clinical significance of genetic polymorphisms of IL-6 (−634G>C) and IL-6R (48892A>C) in NSCLC patients treated with ICIs.…”
Section: Clinical Significance Of Plasma Il-6 Levels In Non-small Cel...mentioning
confidence: 99%
“…It has been reported that IL-6 (−634G>C) and IL-6R (48892A>C) genetic polymorphisms are associated with the risk or prognosis in patients with some cancers ( DeMichele et al, 2009 ; Motoyama et al, 2012 ; Stephens et al, 2012 ; Kibe et al, 2014 ; Ruzzo et al, 2014 ; Zhang et al, 2017 ; Gu et al, 2023 ). For example, we previously demonstrated that the IL-6 (−634G>C) genetic polymorphism showed a significant association with prognosis after surgery in advanced thoracic esophageal squamous cell carcinoma ( Motoyama et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%